Mathematical modelling of grain production profitability in Ukraine taking into account risks. (2017) - Hrytsiuk, Petro Mykhailovych; Babych, Tetiana Yuriivna
Ukraine is an agrarian state. One of the most important branches of agriculture sector is grain production. High yield of grain is a basis of Ukrainian food security. Therefore the task of developing a reliable mathematical model forecasting the grain production profitability is urgent. Regression analysis and fuzzy simulation principles have been used for building a grain production profitability depending model from crop production in the last two years, average price of grain in the country and grain production costs. The values of profitability forecasting for 2015 obtained by three different methods are convergent to each other. Contribution of factors' changes such as yield, the price of grain and the cost of grain production into fluctuation of grain production profitability have been also analysed.